Work-related stress: A survey of Indian anesthesiologists - Sumitra Ganesh Bakshi; Jigeeshu Vasishtha Divatia; Sadhana Kannan; Sheila Nainan Myatra (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: Work-related stress is common among medical caregivers and concerns all perioperative care providers. Although anesthesiologists are known to experience stress, there are limited Indian data addressing this issue. This survey was conducted among Indian anesthesiologists to determine their awareness about work stress and views regarding prevention programs. Material and Methods: A survey questionnaire was distributed to delegates visiting the exhibits at the national anesthesiology conference in 2011. The questionnaire had ten questions on the work pattern, five on work-related stress, nine on opinion regarding the need and willingness to participate in stress-related programs. Results: There were 1178 responders. Forty-three percent were faculty in medical institutions, 26% were residents and 25% were in free-lance practice. Ninety-one percent of participants rated their stress as moderate-extreme. There was a significant correlation between the amount of stress and working for more than 8 h (P < 0.001), handling high risk patients (P = 0.002), working on weekends (P = 0.002), and carrying work back home (P < 0.001). Forty-one percent of respondents were very satisfied professionally. Seventy-six percent of doctors agreed that the questionnaire had made them think about work stress. Eighty-four percent of participants felt the need for stress management programs and 69% expressed their willingness to participate in the same. Conclusion: The majority of participants rated their stress as moderate-extreme and was higher in anesthesiologists working long hours, over the weekend and those handling high-risk patients. A majority of participants felt the survey made them think about work-related stress and expressed their willingness to participate in stress management programs.